Alcohol policy and regulation: public opinion amongst young adults in Khayelitsha, South Africa - Ferrell, Britany (Department of Public Health and Family Medicine, 2016)
South Africa has one of the highest rates of alcohol consumption in the world. It is important to study public opinion of alcohol regulatory policies as it plays a crucial role in the success of policy measures. There is a dearth of research on public opinion of alcohol policies in developing countries. This study is the first to explore public opinion of older and young adults on alcohol policy in South Africa. In addition, the drinking behavior of young adults was also investigated along with its relationship with policy support. Methods: The study sample consisted of 1728 young (n=513) and older adults (n=1215). Demographic details and opinion on 15 policy measures (Yes/No) were recorded for both groups. The survey of young adults included additional questions on drinking patterns. Univariate analysis of opinion on policy measures was performed for each group and compared using chi-square tests. Logistic regression was used to find the relationship between policy support levels and demographic factors and drinking behavior of young adults. Results: Complete data were recorded for 567 older adults and 402 younger adults. The majority of the participants (75-80 percent) agreed on restricted availability, increased pricing and greater enforcement measures. In contrast, only 65% of the participants were in favor of increased restrictions on alcohol marketing. Older adults were more supportive of earlier closing times of bars, a raise in minimum purchasing age, as well as an increase in pricing and taxes of alcohol (p<0.001). Females and employed participants were found to be more likely to support alcohol policy measures. Drinking patterns and behavior of young adults significantly predicted most policy measures after controlling for demographic factors. For example, policies on restricted alcohol availability, increase in taxes, and raids were supported by participants who reported that they mostly drank at big events. In contrast, these policies were opposed by those who drink alcohol every day and almost every day along with those who drink during street bashes Support for restrictions on the purchase age of alcohol was not predicted by drinking patterns of young adults Conclusion: It is important to increase the understanding and support of vulnerable groups, especially males and young adults, for policy measures. The relationship between drinking patterns and policy support levels indicates that regular tracking of drinking behavior is necessary for the success of these policies. The results support previous findings indicating that young people are more likely to resist alcohol regulations.